Vibration of hollow fibre membranes in submerged membrane bio-reactors (SMBRs) - Li, Tian (2015)
In this study, the improvement of fouling control of submerged hollow fibre membrane filtration with mechanical sinusoidal vibration was examined experimentally in the dead-end filtration of inorganic Bentonite and organic yeast suspensions, as well as mixed liquor collected from a local water reclamation plant. The hollow fibre membranes were submerged in the reactor and vibrated both longitudinally and transversely.